WACANA ISRAILIYYAT DALAM KITAB MAHASIN AL-TA’WIL KARYA AL-QASIMI - Idris Idris; Harfin Harfin; Subaidi Subaidi (UIN Siber Syekh Nurjati Cirebon, 2021)
This article discusses about israiliyyat story opus by Jamaluddin al-Qasimi in his interpretation's book Mahasin al-Ta’wil. The method used in measuring validity or not, the author uses the standard al-naqd al-matn, because most of the history of israiliyyat by al-Qasimi is not accompanied by sanad or reference sources. The author examines nine narrations of israiliyyat t from the book of Mahasin al-Ta’wil with the standard method of criticism matan. The result: (a) three history of israiliyyat is considered sahih, namely: in verse 50, 51 surah al-Baqarah, and verse 36 surah Yusuf, (b) four narrations of israiliyyat are considered maskut ‘anhu, namely: in verse 54 surah al-Baqarah, verse 155 surah al-A'raf, preamble surah Yusuf and verse 54 surah Yusuf, (c) two narrations israiliyyat is considered vanity, namely: in paragraphs 142 and 155 surah al-A'raf. So, Mahasin al-Ta’wil is considered unclean from al-dakhil source, because the source israiliyyat which is judged to be invalid and maskut'anhu.